Pengaruh Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan di Puslatbang PKASN LAN - Kadar MD, Muhamad; Dewi Pramanik, Nuniek (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to ascertain the extent to which human resource development influences employee performance at PUSLATBANG PKASN LAN. In this research, data gathered via staff questionnaire distribution at PUSLATBANG PKASN LAN were analyzed using a quantitative descriptive approach. This research used the T-test, coefficient of determination, multicollinearity, linearity, heteroscedasticity, validity, reliability, and normality tests. In addition, this study demonstrates how employee performance is impacted by human resource development. Employee performance is significantly impacted by human resource development, according to study supported by the SPSS 24 program. This is shown by the t test findings, which show that variable x affects variable y as the computed t value is higher than the t table (2.970 > 1.697).